Oxidative stress and inflammation distinctly drive molecular mechanisms of diastolic dysfunction and remodeling in female and male heart failure with preserved ejection fraction rats - Zhazykbayeva, Saltanat; Hassoun, Roua; Herwig, Melissa; Budde, Heidi; Kovács, Árpád; Mannherz, Hans Georg; El-Battrawy, Ibrahim; Tóth, Attila; Schmidt, Wolfgang E.; Mügge, Andreas; Hamdani, Nazha (Frontiers in Cardiovascular Medicine, 2023)
Heart failure with preserved ejection fraction (HFpEF) is a complex cardiovascular insufficiency syndrome presenting with an ejection fraction (EF) of greater than 50% along with different proinflammatory and metabolic co-morbidities. Despite previous work provided key insights into our understanding of HFpEF, effective treatments are still limited. In the current study we attempted to unravel the molecular basis of sex-dependent differences in HFpEF pathology. We analyzed left ventricular samples from 1-year-old female and male transgenic (TG) rats homozygous for the mouse Ren-2 renin gene (mRen2) characterized with hypertension and diastolic dysfunction and compared it to age-matched female and male wild type rats (WT) served as control. Cardiomyocytes from female and male TG rats exhibited an elevated titin-based stiffness (Fpassive), which was corrected to control level upon treatment with reduced glutathione indicating titin oxidation. This was accompanied with high levels of oxidative stress in TG rats with more prominent effects in female group. In vitro supplementation with heat shock proteins (HSPs) reversed the elevated Fpassive indicating restoration of their cytoprotective function. Furthermore, the TG group exhibited high levels of proinflammatory cytokines with significant alterations in apoptotic and autophagy pathways in both sexes. Distinct alterations in several molecular parameters between both sexes suggest their differential impact on disease development and necessitate distinct treatment options. Hence, our data suggested that oxidative stress and inflammation distinctly drive diastolic dysfunction and remodeling in female and male rats with HFpEF and that the sex-dependent mechanisms contribute to HF pathology